2012
DOI: 10.1007/s00464-012-2310-8
|View full text |Cite
|
Sign up to set email alerts
|

The degree of gallbladder wall thickness and its impact on outcomes after laparoscopic cholecystectomy

Abstract: A greater degree of gallbladder wall thickness is associated with an increased risk of conversion, increased postoperative complications, and longer lengths of stay. Classifying patients according to degree of gallbladder wall thickness gives more accurate assessment of the risk of surgery, as well as potential outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 24 publications
2
38
2
2
Order By: Relevance
“…Gall bladder wall thickness is not a good indicator of mucosal hyperplasia or cholecystitis in dogs, 20,26 although in people, gall bladder wall thickness can be predictive of laparoscopic operability. 27,28 Two dogs that required open cholecystectomy had a gall bladder wall thickness greater than normal (2-3 mm). 21,29 Preoperative abdominal ultrasound examination showed evidence of localized inflammation around the cystic duct in 1 dog.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gall bladder wall thickness is not a good indicator of mucosal hyperplasia or cholecystitis in dogs, 20,26 although in people, gall bladder wall thickness can be predictive of laparoscopic operability. 27,28 Two dogs that required open cholecystectomy had a gall bladder wall thickness greater than normal (2-3 mm). 21,29 Preoperative abdominal ultrasound examination showed evidence of localized inflammation around the cystic duct in 1 dog.…”
Section: Discussionmentioning
confidence: 99%
“…24,50 Predictive factors for conversion to open cholecystectomy in people include increased white blood cell count, ultrasound findings of pericholecystic fluid, low serum albumin, elevated serum total bilirubin, right cranial abdominal pain during ultrasound, being male, obesity, comorbidities, and the presence of a thickened gall bladder wall. 13,28,31,49 Since the pathogenesis of disease differs in canines, [9][10][11][12]19,22 extrapolation of risk factors from people is not possible; however, careful consideration of preoperative imaging and the clinical status of the dog is imperative for successful laparoscopic cholecystectomy. We did not find any factors related to conversion to open cholecystecomy in our study.…”
Section: Discussionmentioning
confidence: 99%
“…As far as surgical outcomes go, a conversion rate of 4% and surgical and medical complication rate of 1% and 10%, respectively, is in keeping with the rates reported in the literature. 20 Some studies show poorer outcomes based on gallbladder wall thickness 20,21 and delayed surgery. Our study showed that wall thickness of 5 mm or more was associated with acute cholecystitis, necrosis and increased duration of surgery, but conversions, complications and length of stay were similar.…”
Section: Discussionmentioning
confidence: 99%
“…Increased thickness of the gallbladder wall up to 9 mm (normal #3 mm) 17,18 was seen in 10 patients (29%). Eight patients (24%) had polyps with a diameter exceeding 5 mm in 6 patients, with a maximum of 13 mm (table 1).…”
mentioning
confidence: 99%